2016
DOI: 10.1038/srep38401
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation variations after short-term heat shock treatment in cultured microspores of Brassica napus cv. Topas

Abstract: Heat stress can induce the cultured microspores into embryogenesis. In this study, whole genome bisulphite sequencing was employed to study global DNA methylation variations after short-term heat shock (STHS) treatments in cultured microspores of Brassica napus cv. Topas. Our results indicated that treatment on cultured Topas microspores at 32 °C for 6 h triggered DNA hypomethylation, particularly in the CG and CHG contexts. And the total number of T32 (Topas 32 °C for 6 h) vs. T0 (Topas 0 h) differentially me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 51 publications
5
45
0
Order By: Relevance
“…For all the sequences, the methylation density under the CG context was the highest, followed by that under the CHG and CHH contexts, which is consistent with two other reports on rapeseed [ 1 , 35 ]. The DNA methylation level varies among different tissues and organs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For all the sequences, the methylation density under the CG context was the highest, followed by that under the CHG and CHH contexts, which is consistent with two other reports on rapeseed [ 1 , 35 ]. The DNA methylation level varies among different tissues and organs.…”
Section: Discussionsupporting
confidence: 91%
“…Chalhoub et al observed that C n genes presented 4% to 8% higher methylation than their homologous A n genes from the methyl bisulfite sequencing of roots and leaves [ 1 ]. A similar result was obtained in cultured microspores by Li et al: the amount of methylated cytosines distributed on the C n subgenome was obviously larger than that distributed on the A n subgenome [ 35 ]. It was hypothesized that the different DNA methylation levels between the A n and C n subgenomes can be attributed to the asymmetrical distribution of TE density in the genome of B. napus .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…oleracea methylome [ 49 ]. Further, only a limited number of studies have assessed the potential involvement of altered DNA methylation under heat stress [ 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Methylation enhanced more in the heat-sensitive genotype than in the heat tolerant genotype under heat treatments. It is reported that more changes in the DNA methylation status of cultured microspores were observed under high temperature [259].…”
Section: Epigenetics and Heat Tolerancementioning
confidence: 99%